Pendugaan Akuifer dengan Geolistrik dan Pemetaan Geologi Ceporan, Klaten - Marsyom, Insern Loisa (ReTII, 2025)
This research was conducted in Ceporan Village, Gantiwarno District, Klaten Regency, Central Java Province. The aim was to identify aquifer potential using the Schlumber configuration geoelectric method and surface mapping, including lithology, porosity, and permeability data. The geoelectric method was used to determine subsurface conditions through variations in resistivity values, and surface mapping was used to identify the exposed lithology and the porosity and permeability of the rocks. The main problem addressed in this study was the subsurface conditions in the study area and the potential for aquifers based on the resistivity characteristics of the rocks. Interpretation results indicate the presence of rock layers consisting of sediment, silt-clay, clay, sandstone, claystone, siltstone, and andesite breccia. Analysis results indicate the presence of a sandstone layer at a depth of 3-25 meters, interpreted as a potential aquifer zone. This research is expected to serve as a basis for planning sustainable groundwater resource management in the southern Klaten region, especially in the Ceporan area. Keyword : Geoelectric, Aquifer, Resistivity, Mapping